Visual Design of Chinese Animated Films Infused with Oriental Punk Aesthetics - Jin, Jiasheng; Sharudin, Sharul Azim; Wang, Tingting (Journal of Theory and Practice of Social Science, 2024)
In recent years, China's movie industry has been advancing, and movies based on ancient myths, which can combine cultural expression with technical expression, have become a hot topic for creation. Especially the ancient mythological novels such as "The Legend of Deification" and "Journey to the West" have become the source of creative ideas for movie adaptations, and Light Chaser Animation, as one of the most important forces in Chinese film production, has been exploring new possibilities for animation movies, inheriting and innovating traditional Chinese cultural elements. Light Chaser Animation, as one of the most important forces in Chinese film production, has been exploring new possibilities for animation films, inheriting and innovating traditional Chinese cultural elements, and has produced the famous "New Gods" series of films, which combines oriental elements and cultural characteristics, blends modernity and tradition, and forms an Oriental Punk style with Chinese characteristics. Oriental Punk not only shows the construction of modernity of Chinese traditional culture, but also the embodiment of cultural self-confidence, and at the same time presents the unique style and aesthetic value of Chinese culture to the world. This article analyzes the visual symbols, color design and action vocabulary of the film New Gods: Yang Jian, and points out a new direction for Chinese films to integrate traditional cultural elements and modern art technology in the creation of new mythological themes.